2010
DOI: 10.1007/s00703-010-0086-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of coastal winds along the central west coast of India using the MM5 mesoscale model

Abstract: High resolution mesoscale model (MM5) has been used to study the coastal atmospheric circulation of central west coast of India, and Goa in particular. The model is employed with three nested domains. The innermost domain of 3km mesh covers Goa and the surrounding region. Simulations have been carried out for three different seasons -northeast (NE) monsoon, transition period and southwest (SW) monsoon with appropriate physics options to understand the coastal wind system. Simulated wind speed and direction mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Large-scale flow is characterized by the strong onshore winds that intensify the sea breeze in this period. Such an effect of the synoptic flow has been observed by Pushpadas et al (2010) in a numerical model for the west coast of India.…”
Section: Sea Breezes Strengthmentioning
confidence: 83%
See 3 more Smart Citations
“…Large-scale flow is characterized by the strong onshore winds that intensify the sea breeze in this period. Such an effect of the synoptic flow has been observed by Pushpadas et al (2010) in a numerical model for the west coast of India.…”
Section: Sea Breezes Strengthmentioning
confidence: 83%
“…Such an effect of the synoptic flow has been observed by Pushpadas et al . () in a numerical model for the west coast of India.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most observational and modeling studies emphasize on general SB characterization and impacts on transport and dispersion of air pollutants. Atmospheric or meteorological modeling has also aided investigating the time-dependent vertical structure of SB in both horizontal and vertical spatial scales, and on physical processes involved (e.g., Lin et al 2001;Ding et al 2004;Srinivas et al 2006;Pushpadas et al 2010). Arritt (1992) reported that prevailing onshore synoptic winds of a few meters per second (or larger) are sufficient to suppress SB development, while it is still possible for an SB to develop under strong offshore (opposing) synoptic winds (as strong as 11 m/s).…”
Section: Introductionmentioning
confidence: 99%